Synthesis and characterization of functional copolymer/organo-silicate nanoarchitectures through interlamellar complex-radical (co)terpolymerization (eXPRESS Polymer Letters)
The functional copolymers, having a combination of rigid/flexible linkages and an ability of complex-formation with interlayered surface of organo-silicate, and their nanocomposites have been synthesized by interlamellar complex-radical (co)terpolymerization of intercalated monomer complexes of maleic anhydride (MA) and itaconic acid (IA) with dimethyl dodecylamine surface modified montmorillonite (organo-MMT) (MA…DMDA-MMT and IA…DMDA-MMT) n-butyl methacrylate (BMA) and/or BMA/styrene monomer mixtures. The results of nanocomposite structure–composition– property relationship studies indicate that interlamellar complex-formation between anhydride/acid units and surface alkyl amine and rigid/flexible linkage balance in polymer chains are important factors providing the effective intercalation/ exfoliation of the polymer chains into the silicate galleries, the formation of nanostructural hybrids with higher thermal stability, dynamic mechanical behaviour and well dispersed morphology.